Concepts of chemical engineering for chemists - Simons, Stefaan J. R. (Royal Society of Chemistry, 2017)
This publication gives chemists an insight into the world of chemical engineering, outlining the basic concepts and explaining the terminology of, and systems approach to, process design. It does not focus on derivation of mathematical formulae, but rather on the governing principles, explaining and demonstrating their use.